Peningkatan Mutu Pembelajaran Bahasa Arab Berbasis Aktivitas Di Madrasah Ibtidaiyah - Imam Makruf; Anisatul Barokah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2020)
Implementing the 2013 curriculum, these madrassas have generally begun to apply scientific learning. However, it still cannot be carried out optimally. This article aims to find out the improvement in the quality of Arabic learning in MI (Madrasah Ibtidaiyah) in Kartasura District which is characterized by an increase in teacher skills in developing activity-based Arabic learning strategies, the variety of learning activities, the activeness of students in participating in learning and increasing the ability of Arabic language learners. By using the Service-Learning approach which is integrated with Participatory Action Research with the main stages of preparation or planning, serving or action, and evaluation or reflection. There were 8 madrasas in Kartasura District being observed. Data were collected by observation, interview and documentation, and validated by a focused group discussion. The results of this research show that; the teachers apply various learning activities that are varied for each maharah although the intensity and variation varies. Among the learning activities of mahārah istimā’-kalām is the reinforcement of memorization of Arabic vocabulary and expressions using drill or istimā’-kalām, singing, and word chain. Mahārah qirā'ah has more activities involving reading out loud classically, whether in large groups, small groups, or individual loud reading activities, chain reading, and reading with media such as LCDs, cards, or objects that are given Arabic names. For maharah kitabah, the most widely used activity is imla', follow the line, stringing words into sentences, and guided writing through assignments. The activeness of the students in participating in learning also increased, although not too significantly. Likewise with the activeness and ability of Arabic language. After implementing the activity-based learning, the students the language ability has also increased. Keywords: Quality Improvement, Learning Activities, Madrasah Ibtidaiyah